The Effect of Circuit Training on Word Performance in Forki Palembang Karate Athletes - Fariz Pramana Sastra; Yasir Arafat; Putri Cicilia Kristina (CV. Rayyan Dwi Bharata, 2022)
This study aims to determine the effect of circuit training ont the performance of karate athletes FORKI Palembang. The type and design of the research used in this study is a quantitative study with a One Group Pre-test Post-test research design. The subjects in this study were karate kata athletes, especially 20 kata athletes of cadet to senior age at the Wadokai Central Dojo Palembang. The data analysis techniques in this study were normality test, homogeneity test, and t-test using the paired sample t-test.The result of the research on the effect of circuit training on kata performance on FORKI Palembang karate athletes were obtained from the paired sample t-test, namely sig (2-tailed) 0,000 0.05. these result indicate that the hypothesis is accepted, which means that there is an effect of circuit training on kata performance in FORKI Palembang karate athletes.